Inpatient rehabilitation for a patient with COVID-19 exacerbation of pulmonary fibrosis: a case report - Heather McKenna; Erin Y. Harmon (Journal of Rehabilitation Medicine - Clinical Communications)
Objective: To evaluate the benefits of inpatient rehabilitation for a patient with post-COVID-19 pulmonary fibrosis and to provide guidance for rehabilitation professionals, as many conventional therapeutic interventions are not tolerated and are poorly defined.